Self‐pollination and parthenocarpic ability in developing ovaries of self‐incompatible Clementine mandarins (Citrus clementina). Issue 1 (26th October 2012) - Mesejo, Carlos; Yuste, Roberto; Martínez‐Fuentes, Amparo; Reig, Carmina; Iglesias, Domingo J.; Primo‐Millo, Eduardo; Agustí, Manuel
<x xml:space="preserve">Abstract</x> This study aimed to determine if self‐pollination is needed to trigger facultative parthenocarpy in self‐incompatible Clementine mandarins (Citrus clementina Hort. ex Tan.). 'Marisol' and 'Clemenules' mandarins were selected, and self‐pollinated and un‐pollinated flowers from both cultivars were used for comparison. These mandarins are always seedless after self‐pollination and show high and low ability to develop substantial parthenocarpic fruits, respectively. The time‐course for pollen grain germination, tube growth and ovule abortion was analyzed as well as that for carbohydrates, active gibberellins (GA1 and GA4), auxin (IAA) and abscisic acid (ABA) content in the ovary. 'Clemenules' showed higher pollen grain germination, but pollen tube development was arrested in the upper style 9 days after pollination in both cultivars. Self‐pollination did not stimulate parthenocarpy, whereas both un‐pollinated and self‐pollinated ovaries set fruit regardless of the cultivar. On the other hand, 'Marisol' un‐pollinated flowers showed greater parthenocarpic ovary growth than 'Clemenules' un‐pollinated flowers, i.e. higher ovule abortion rate (+21%), higher fruit set (+44%) and higher fruit weight (+50%). Further, the greater parthenocarpic ability of 'Marisol' paralleled higher levels of GA1 in the ovary (+34% at anthesis). 'Marisol' ovary also showed higher hexoses and starch mobilization, but lower ABA levels (−64% at anthesis). Self‐pollination did not modify carbohydrates or GA content in the ovary compared to un‐pollination. Results indicate that parthenocarpy in the Clementine mandarin is pollination‐independent with its ability to set depending on the ovary hormone levels. These findings suggest that parthenocarpy in fertile self‐incompatible mandarins is constitutively regulated.